Some effects of non-normal distribution shape on the magnitude of the Pearson Moment Correlation Coefficient - Calkins, Dick S. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
All correlational statistics must be interpreted with consideration given to certain constraints. The use of the Pearson product moment correlation coefficient as a descriptive measure of relationship necessitates the assumption that the correlated variables be distributed bivariately normal. This assumption is probably not met in some applications of the Pearson product moment correlation coefficient as a descriptive statistic. This study was undertaken to establish some empirical evidence as to the consequences of this action. The results indicate that lack of bivariate normality can have a sizeable effect on the magnitude of obtained values of the Pearson product moment correlation coefficient.